2022
DOI: 10.3390/antiox11122376
|View full text |Cite
|
Sign up to set email alerts
|

Colon-Targeted eNAMPT-Specific Peptide Systems for Treatment of DSS-Induced Acute and Chronic Colitis in Mouse

Abstract: Nicotinamide phosphoribosyl transferase (NAMPT) is required to maintain the NAD+ pool, among which extracellular (e) NAMPT is associated with inflammation, mainly mediated by macrophages. However, the role of (e) NAMPT in inflammatory macrophages in ulcerative colitis is insufficiently understood. Here our analyses of single-cell RNA-seq data revealed that the levels of NAMPT and CYBB/NOX2 in macrophages were elevated in patients with colitis and in mouse models of acute and chronic colitis. These findings ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…The latter findings were recently confirmed by Kim et al. ( 95 ), who showed that the 57–65 aa region of eNAMPT interacts with the leucine-rich repeats (LRR) domain of TLR4. A putative TLR4-binding site in the C-terminal region of eNAMPT (445–457 aa) has also been identified ( 96 ).…”
Section: Enampt Cell Surface Receptorsmentioning
confidence: 53%
See 1 more Smart Citation
“…The latter findings were recently confirmed by Kim et al. ( 95 ), who showed that the 57–65 aa region of eNAMPT interacts with the leucine-rich repeats (LRR) domain of TLR4. A putative TLR4-binding site in the C-terminal region of eNAMPT (445–457 aa) has also been identified ( 96 ).…”
Section: Enampt Cell Surface Receptorsmentioning
confidence: 53%
“…Using site-directed mutagenesis, the authors identified two regions in the N-terminal part of eNAMPT that are involved in TLR4 binding (b1-b2 loop: 41-52 aa; and a1-a2 loop: 68-77 aa). The latter findings were recently confirmed by Kim et al (95), who showed that the 57-65 aa region of eNAMPT interacts with the leucine-rich repeats (LRR) domain of TLR4. A putative TLR4-binding site in the C-terminal region of eNAMPT (445-457 aa) has also been identified (96).…”
Section: Enampt Cell Surface Receptorsmentioning
confidence: 56%
“…All available data thus provide evidence of neutrophil activation being crucial to KD pathogenesis. Furthermore, it has been observed that IL1B, SOCS3, and IL1RN exhibit high expression levels in other autoimmune diseases that are closely linked to impaired innate immune function [69].…”
Section: Discussionmentioning
confidence: 99%
“…Using public single-cell datasets, our previous study identified key driver genes in macrophages associated with IBD in humans and mouse models through Nampt . Notably, we identified and validated that eNAMPT interact with Tlr4 or Cybb /NOX2 and activate NLRP3 inflammasome in IBD tissues 5 . By understanding the relationship between dysbiotic communities and host immune response, we revealed a crucial role for Nlrp3 / Nampt .…”
Section: Introductionmentioning
confidence: 87%